Self-Assembly of Homo-Polyarylene Ether Into Reactive Matrix for Fabrication of Hybrid Functional Microparticles - Gong, Du; Zhang, Dawei; Zhang, Xiaoying; He, Xiaohong; Ji, Yao; Jia, Kun (Frontiers in Chemistry, 2022)
Emulsion confinement self-assembly of block copolymer has witnessed increasing research interests in recent decade, but the post-functionalization and application of the resultant polymeric microparticles is still in its infancy. In this work, a super-engineering polyarylene ether containing pendent nitrile and carboxyl (PAE-NC) has been synthesized and converted into polymeric microparticles for antibody accumulation via emulsion confinement self-assembly. Meanwhile, the encapsulation capacity of PAE-NC was evaluated using hydrophobic fluorescent quantum dots (QD) as functional probe. Specifically, we found that both the as-synthesized PAE-NC and its hydrolysed derivatives could be converted into microparticles via emulsion confinement self-assembly. Furthermore, the co-self-assembly of red-emitting QD and PAE-NC enables the phase transfer of hydrophobic QD into hydrophilic luminescent microparticles with persisted fluorescence emission. Based on these results, the current PAE-NC would be served as versatile and robust scaffold to fabricate advanced microcapsules for various applications.